Heavy metal and nitrogen concentrations in mosses are declining across Europe whilst some "hotspots" remain in 2010 - Harmens, H; Norris, D A; Sharps, K; Mills, G; Alber, R; Aleksiayenak, Y; Blum, O; Cucu-Man, S-M; Dam, M; De Temmerman, L; Ene, A; Fernández, J A; et al. (My University, 2015)
In recent decades, naturally growing mosses have been used successfully as biomonitors of atmospheric deposition of heavy metals and nitrogen. Since 1990, the European moss survey has been repeated at five-yearly intervals. In 2010, the lowest concentrations of metals and nitrogen in mosses were generally found in northern Europe, whereas the highest concentrations were observed in (south-)eastern Europe for metals and the central belt for nitrogen. Averaged across Europe, since 1990, the median concentration in mosses has declined the most for lead (77%), followed by vanadium (55%), cadmium (51%), chromium (43%), zinc (34%), nickel (33%), iron (27%), arsenic (21%, since 1995), mercury (14%, since 1995) and copper (11%). Between 2005 and 2010, the decline ranged from 6% for copper to 36% for lead; for nitrogen the decline was 5%. Despite the Europe-wide decline, no changes or increases have been observed between 2005 and 2010 in some (regions of) countries.